Invariant genres in literature and art (Eurasian Journal of Philology Science and Education, 2023)
Introduction. The subject of study are invariant genres in literature and art. This topic is considered on the example of Bakhyt Kairbekov. The purpose of the study is to substantiate the proposed hypothesis that the most important feature of the creative evolution of Bakhyt Kairbekov as a director, screenwriter, and poet is genre identity, appeal to both traditional and «border» genres. The main directions and the leading ideas of scientific research are the analysis and synthesis of invariant forms of works, revealing in them the signs of artistry, journalism, documentary; definition of the author’s consciousness as a genre-forming factor. The scientific significance of the work is contained in the theses on the predominance of prosodic organization and lexical syntactic structure of cinema discourse and essay of mentally conditioned concepts. The methodology of the study is based on an interdisciplinary approach, the use of art and linguistic methods of analysis, revealing in the studied works the correlation of video-verbal and linguistic characteristics. The main results and analysis of materials in this research work are traced in theses about the typological diversity and specificity of the genre structure of Bakhyt Kairbekov’s works. The article formulates two main conclusions: documentaries are invariant forms that incorporate elements of the film, monologue film, film-review; essay studies thematically overlap with documentaries, content dominant essays coincide with philosophical reflections of the author. The value of the study and the contribution of this work to the philological field of knowledge lies in the originality of the chosen approach, in which both artistic texts and genres of documentary film are studied. Practical significance of the work: its results can be used in the educational process, in the study and teaching of the disciplines of the literary cycle.                                                                                                                                Key words: genre, invariant, typology, documentary film, essay, author’s consciousness.